MALLORY WEISS SYNDROME IN DIFFUSE LIVER LESIONS - Xalimova Yulduz Salokhiddinovna (Journal of Science in Medicine and Life, 2023)
Esophageal-gastric bleeding is one of the most common complications of diseases of the gastrointestinal tract caused by liver pathology with the development of portal hypertension. The paper presents the results of complex diagnostics and treatment of patients with bleeding from the upper gastrointestinal tract of varicose and non-varicose character.